Early thiopurine maintenance is associated with reduced proximal disease progression and colectomy rate in ulcerative colitis. Issue 12 (December 2021) - Kariyawasam, Viraj C.; Mourad, Fadi H.; Mitrev, Nikola; Paramsothy, Sudarshan; Selinger, Christian P.; Katelaris, Peter H.; Jones, Brian; McDonald, Charles; Barr, Gavin; Chapman, Grace; Cowlishaw, James; Andrews, Jane; et al.
Abstract : Background: Thiopurines effectively maintain remission in ulcerative colitis patients. Whether early initiation of thiopurines after ulcerative colitis diagnosis decreases proximal disease progression and colectomy rates is not known. Methods: We conducted a cohort study of ulcerative colitis subjects recruited from 1970 to 2009. Early thiopurine maintenance was defined as commencement of azathioprine or mercaptopurine within 5 years of diagnosis and maintenance for at least 6 months. Propensity score matching was conducted to correct for confounders influencing early thiopurine introduction. Outcomes of interest were colectomy rate and endoscopic proximal disease extension. Results: 982 consecutive ulcerative colitis subjects (12 879 patient-years) were recruited with 116 requiring colectomy. Thiopurines initiation and maintenance increased over time with median time to thiopurine commencement decreasing from 23 years in the first decade to 2 years in the last decade ( P < 0.0001). Multivariate analysis showed that early thiopurine maintenance significantly decreased the need for colectomy [hazard ratio, 0.13; 95% confidence interval (CI):0.03–0.55; P = 0.006]. The number of subjects needed to be treated to reduce one colectomy at 5 and 10 years was 18 (95% CI, 16– 36) and 12 (95% CI, 11–25). After propensity score matching, early thiopurine maintenance was significantly associated with decreased colectomy (hazard ratio, 0.10; 95% CI, 0.03–0.43; P = 0.002) and proximal progression of disease extent (hazard ratio, 0.26; 95% CI, 0.10–0.78; P = 0.015). Conclusion: Early thiopurine maintenance for >6 months is significantly associated with reduced colectomy and proximal progression of disease extent in ulcerative colitis. Abstract : Supplemental Digital Content is available in the text.